The glass artist's studio handbook : traditional and contemporary techniques for working with glass - Cohen, Cecilia (Beverly, Mass. : Quarry Books, 2011)
"The Glass Artist's Studio Handbook offers readers a comprehensive and accessible guide to not only the nuts and bolts of this perennially popular craft but insight into the artisan crafter's lifestyle. Our book offers much, much more than "just projects" - it will fast become the go-to reference for all home crafters. Many glass art how-to books on the market provide precise patterns and instructions for projects that are fairly traditional in technique, materials and style. Completing a project from those books leaves you with a piece that is ideally identical to what the author created - and to what every other student using the book created. Many books are strong in the basics but do not do enough to challenge us to stretch our imagination, experiment with new styles, and explore materials. Readers want creative challenge and stimulation, and Quarry delivers with this complete glass art curriculum"--
Includes bibliographical references and index.
Keywords: Glass blowing and working